Further Validation of the Female Sexual Function Index: Specificity and Associations With Clinical Interview Data. Issue 5 (3rd July 2016) - Stephenson, Kyle R.; Toorabally, Nasreen; Lyons, Leah; M. Meston, Cindy
Abstract : Female sexual function is a multi-faceted psychophysiological construct. The Female Sexual Function Index (FSFI) is considered a "gold standard" self-report instrument that assesses the various aspects of sexual function. However, researchers have recently proposed potential limitations of the FSFI, highlighting the need for continued validation research. The aims of the current analyses were (a) to assess the correlations between FSFI scores and information regarding specific rates of functional impairment gained via clinical interview; and (b) to assess the specificity of FSFI subscale scores in reflecting corresponding aspects of sexual function (e.g., whether the Sexual Desire subscale reflects sexual desire specifically rather than sexual arousal, orgasm, etc.). The participants were 97 sexually active women who reported impairments in sexual function. Clinical interview data exhibited moderate-to-strong correlations with FSFI scores. Additionally, FSFI subscales generally exhibited adequate specificity in terms of reflecting their corresponding aspects of sexual function more strongly than other aspects. The results generally supported the validity of the FSFI. Implications for the measurement and conceptualization of female sexual function are discussed.